Preparation method of phase-change energy-storage waterborne polyurethane nanofiber membrane

The phase-change energy-storage water-based polyurethane nanofiber membrane is prepared by using silicone modified water-based polyurethane and lignin-based phase-change microcapsules combined with electrospinning technology, and undergoing plasma hydrophobic modification, the solvent pollution and inhomogeneity problems in the electrospinning process are solved, and efficient and environmentally friendly nanofiber membrane preparation is achieved, suitable for personal thermal management textiles.

CN119640499AActive Publication Date: 2025-03-18SHISHI JIANAN HOT MELT ADHESIVE CO LTD

Patent Information

Application Number
CN202411853316.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The prior art solvent pollution problems in the preparation electrospinning process and the inhomogeneity and inefficiency problems in the aqueous polyurethane spinning process are difficult to meet the needs of environmentally friendly and efficient preparation.

Method used

Silicone-modified water-based polyurethane is used as raw material to prepare lignin-based phase-change microcapsules through lignin self-assembly and ultraviolet cross-linking, and phase-change energy-storage water-based polyurethane nanofiber membranes are prepared in combination with electrospinning technology, and hydrophobic modification is further carried out through plasma technology to achieve asymmetric wetting.

Benefits of technology

It solves the problem of solvent pollution in traditional electrospinning processes, improves the spinningability and packaging efficiency of the spinning liquid. The prepared nanofiber membrane has good heat storage and heat exogenous properties, water resistance and moisture permeability, and is suitable for personal thermal management textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640499A_ABST
    Figure CN119640499A_ABST
Patent Text Reader

Abstract

The invention discloses a phase change energy storage waterborne polyurethane nanofiber membrane and a preparation method thereof. Lignin-based phase change microcapsules are prepared by combining ultraviolet crosslinking with lignin shell packaging, and then the nanofiber membrane containing the phase change microcapsules is prepared through an electrostatic spinning technology. And finally, constructing the waterborne polyurethane phase change fiber membrane with asymmetric wettability through a low-temperature plasma technology. According to the invention, lignin is self-assembled to form nanoparticles, and ultraviolet light induces free radical polymerization to form a polymer film, so that the packaging capability of the phase change material is improved. The phase change microcapsule prepared by the method is high in packaging efficiency and excellent in phase change performance, the preparation process is green and environment-friendly, the technological operation is simple, the temperature of the prepared phase change energy storage waterborne polyurethane nanofiber membrane conforms to the comfortable temperature range of a human body, and the phase change energy storage waterborne polyurethane nanofiber membrane has excellent temperature regulation, waterproof and moisture permeable performance and is suitable for being used in the field of water treatment. Good application prospects are realized in the field of functional textiles with functions of intelligent temperature regulation, water resistance and air permeability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional membrane materials, and specifically relates to a phase-change energy storage waterborne polyurethane nanofiber membrane and a preparation method thereof. Background Art

[0002] As the trend of global warming accelerates significantly, severe weather such as extreme heat, cold, and storms frequently occur, which poses severe physiological challenges to people who work outdoors for a long time, such as construction workers, farmers, emergency personnel, and outdoor athletes. High temperatures may cause health hazards such as heat stroke and dehydration, while long-term exposure to cold environments may cause hypothermia or even frostbite. Therefore, how to effectively ensure the thermal comfort and health of outdoor workers has become a key area of ​​research in functional textiles in recent years.

[0003] Traditional temperature control methods, such as air conditioning, heating, fans, etc., are mainly used in indoor environments, and outdoor workers cannot enjoy these conveniences. In addition, such equipment consumes a lot of energy and does not meet the requirements of environmental protection and sustainable development. With the increasing global attention to low-carbon economy and energy conservation and environmental protection, Personal Thermal Management (PTM) has gradually become a key strategy for dealing with extreme weather. PTM achieves more precise thermal management by locally adjusting the temperature of the human body surface rather than changing the temperature of the entire environment, which not only saves energy, but also improves the comfort and work efficiency of workers in harsh environments.

[0004] In the research of PTM, the development of intelligent functional textiles has received particular attention. This type of textile can absorb or release heat by combining with phase change materials (PCM) to play a role in automatic temperature regulation. The thermal conductivity of traditional PCM is limited and it is easy to leak during phase transformation. The emergence of phase change microcapsules provides a solution to these problems. Phase change microcapsules contain two parts: PCM as the core and polymer or inorganic shell that encapsulates PCM. In the traditional method of preparing phase change microcapsules, polymer-encapsulated phase change emulsion (W / O) is often used. The emulsion consists of an aqueous phase and an oil phase. The oil phase is a PCM material, and the polymer shell material that encapsulates PCM in the aqueous phase. However, the emulsion has a tendency to separate under natural conditions, so a large amount of surfactants and emulsifiers are required to stabilize the emulsion. The instability of phase change emulsion will lead to low encapsulation efficiency of phase change microcapsules. Polyurethane can be used as a textile coating and is often used to encapsulate phase change materials. CN202411192924 discloses a method for preparing low-temperature phase change microcapsules, using polyurethane as a shell material and a low-temperature phase change material as a core material. The in-situ polymerization method is used to uniformly coat the polyurethane material on the surface of the core material to obtain the low-temperature phase change microcapsules. The prepared microcapsules have good temperature control ability, water resistance, and mechanical properties, but the in-situ polymerization encapsulation efficiency is not high, and the phase change material is easy to leak. Ultraviolet light induces polyurethane free radical polymerization, with fast curing speed, short time, and high encapsulation efficiency. At the same time, lignin can be used as a surfactant and an insoluble shell, and can self-assemble into nanoparticles under acidic conditions. Lignin is added to the emulsion system as a shell material to form a W / O / O two-phase emulsion, which can effectively encapsulate the phase change material. Polyurethane combines with lignin shell to form a double encapsulation, which can effectively prevent the leakage of phase change materials.

[0005] In addition to temperature regulation, outdoor workers often face the problem of discharging a large amount of sweat in a high temperature environment. If sweat cannot be discharged in time, the skin surface will become wet and cold, affecting the comfort of the human body and even causing skin problems. Therefore, smart textiles also need to have good breathability and perspiration functions to ensure that the skin can stay dry. In recent years, fiber materials with asymmetric wettability have gradually attracted attention. This type of material constructs a hydrophilic and hydrophobic structure on both sides of the fiber membrane, where the hydrophilic side is in contact with the skin. When the human body produces sweat, it can achieve one-way transmission of water, help quickly discharge sweat and keep the inside dry, and improve the comfort of wearing.

[0006] Electrospinning technology has shown great application potential in the development of personal thermal management smart textiles. The nanofiber membrane prepared by electrospinning technology has a high specific surface area and a good pore structure. It can be combined with phase change materials to achieve temperature regulation function, and can also enhance the perspiration and moisture permeability of textiles by regulating surface wettability. In addition, the functionalization of the fiber membrane using electrospinning technology according to the use requirements can not only make the material have excellent mechanical properties, but also make it meet the needs of human wear. However, most of the existing electrospinning technologies rely on organic solvents, such as tetrahydrofuran (THF), N,N-dimethylformamide (DMF), trifluoroacetic acid (TFA), dichloromethane (DCM), etc. These solvents will evaporate and leak during the preparation and use process, causing environmental pollution and endangering human health. Therefore, the development of environmentally friendly electrospinning processes has become a hot topic in current research. CN116988225A discloses a preparation method and application of a double-layer phase-change composite fiber membrane, which uses N,N-dimethylformamide to dissolve polyacrylonitrile, adds carbon nanotubes, and prepares a composite phase-change fiber membrane by electrostatic spinning. On this basis, the polyvinylidene fluoride layer is further constructed by electrostatic spinning to successfully prepare a double-layer phase-change fiber membrane. However, this method uses a large amount of organic solvent N'N-dimethylformamide during the preparation process, which will cause environmental pollution and endanger human health. In addition, the outermost vinylidene fluoride layer will have a negative impact on the thermal conductivity of the inner phase-change fiber membrane.

[0007] Waterborne polyurethane is non-toxic and environmentally friendly, and is suitable for preparing PTM coatings. However, water has a high surface tension, high electrical conductivity and a slow evaporation rate. Using water as a solvent can easily lead to uneven thickness of nanofibers prepared by electrospinning. At present, the use of waterborne polyurethane as a raw material and the electrospinning process to prepare waterproof and breathable membranes still requires breakthroughs in some preparation process difficulties. In order to solve the environmental pollution of organic solvents in traditional electrospinning processes and the process problems of waterborne polyurethane spinning during electrospinning, the present invention replaces organic solvents with waterborne polyurethane (WPU), improves the spinning process, reduces the surface tension of water and improves the conductivity of the spinning solution, and develops a green and environmentally friendly electrospinning process for the production of phase change textiles for human thermal management. Further, through plasma surface modification technology, the hydrophobic properties of the fiber membrane are improved, and asymmetric wettability is achieved, thereby meeting the special needs of outdoor workers for textiles in extreme weather. Summary of the invention

[0008] The purpose of the present invention is to provide a phase-change energy storage waterborne polyurethane nanofiber membrane and a preparation method thereof.

[0009] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing a phase-change energy storage waterborne polyurethane nanofiber membrane comprises the following steps: (1) Preparation of lignin-based phase change microcapsules: by weight, add 1 part of alkali lignin to 50-100 parts of sodium hydroxide, then add 2-5 parts of phase change material, and emulsify for 3-10 minutes to obtain an emulsion; mix 1-3 parts of 1,6-hexanediol diacrylate, 1 part of Span80 and 1 part of photoinitiator and add them to the emulsion, continue emulsification for 3-10 minutes, adjust the solution pH to 2-3, irradiate with ultraviolet light for 15 minutes, and finally obtain lignin-based phase change microcapsule powder by spray drying, wherein the wavelength of the ultraviolet light is 365 nm and the intensity is 2000 mW / cm 2 ; (2) preparing a spinning solution: mixing a silicone-modified aqueous polyurethane emulsion, an aqueous thickener, a lignin-based phase change microcapsule powder, a surfactant and an electrolyte, and stirring the mixture at room temperature after ultrasonic dispersion to obtain a spinning solution; (3) Preparing a phase change fiber membrane: injecting the spinning solution into an electrospinning syringe, electrospinning to obtain a nanofiber membrane, and drying to obtain a phase change fiber membrane; (4) Hydrophobic modified phase change fiber membrane: Low-temperature plasma technology is used to perform hydrophobic modification on one side of the phase change fiber membrane.

[0010] Furthermore, the phase change material in step (1) is one or more of polyethylene glycol, paraffin, dodecanol, and octadecane; the amount of phase change microcapsule powder added is 10-25% of the total mass of the silicone-modified aqueous polyurethane emulsion and the aqueous thickener; and the photoinitiator is one or more of 2-hydroxy-2-methylpropiophenone, acryloyl carboxylic acid diester, trimethylbenzoyl-diphenylphosphine oxide, and 2,4-diethylthioxanthone.

[0011] Furthermore, the water-based polyurethane emulsion modified with organic silicon in step (2) is one or more of a water-based polyurethane emulsion modified with vinyl triethoxysilane, a water-based polyurethane emulsion modified with vinyl trimethoxysilane, a water-based polyurethane emulsion modified with γ-glycidyloxypropyl trimethoxysilane, and a water-based polyurethane emulsion modified with γ-aminopropyl methyl diethoxysilane; and the solid content of the water-based polyurethane emulsion modified with organic silicon is 30-50%.

[0012] Furthermore, the aqueous thickener in step (2) is one or more of polyvinyl alcohol, sodium alginate, sodium carboxymethyl cellulose, sodium polyacrylate, and polyvinyl pyrrolidone, and the mass fraction of the aqueous thickener is 10-20%; the mass ratio of the silicone-modified aqueous polyurethane emulsion to the aqueous thickener is 1:1.

[0013] Furthermore, the surfactant in step (2) is one or more of sodium dodecylbenzene sulfonate, polysorbate, fatty acid glyceride, and polyethylene glycol sulfate; the added amount of the surfactant is 0.05-0.1% of the total mass of the silicone-modified aqueous polyurethane emulsion and the aqueous thickener.

[0014] Furthermore, the electrolyte in step (2) is one or more of sodium chloride, sodium bisulfite, hydrogen chloride, and acetic acid; the amount of the electrolyte added is 0.05-0.1% of the total mass of the silicone-modified aqueous polyurethane emulsion and the aqueous thickener.

[0015] Furthermore, the parameters of electrospinning in step (3) are as follows: positive high voltage 15~17kV, negative high voltage -1.5kV, spinning distance 15~20cm, propulsion speed 0.5mm / h, receiving roller speed 60~100r / min, the receiver is a roller covered with silicone oil paper; the spinning environment temperature is 25~30℃, and the humidity is 30~50%.

[0016] Furthermore, in step (4), the gas for low-temperature plasma hydrophobic modification is one of carbon tetrafluoride, tetrafluoroethylene, sulfur hexafluoride, and trimethylfluorosilane; the low-temperature plasma modification power is 50-75 W, and the modification time is 5-10 min.

[0017] A phase-change energy storage waterborne polyurethane phase-change fiber membrane prepared by the above preparation method, wherein the phase-change energy storage waterborne polyurethane phase-change fiber membrane has a phase-change temperature of 13.5-28.5°C, a phase-change enthalpy of 18.0-65.5 J / g, a water droplet contact angle of 140-160° on the hydrophobic side of the phase-change fiber membrane after plasma modification, and a moisture permeability of 1300-2500 g / m 2 ·d, tensile strength is 6.5~11.5MPa, and elongation at break is 255~330%.

[0018] The present invention also provides application of the above-mentioned phase-change energy-storage waterborne polyurethane phase-change fiber membrane in functional textiles.

[0019] The present invention uses organic silicon modified waterborne polyurethane as raw materials, firstly prepares lignin-based phase change microcapsules by lignin self-assembly and ultraviolet crosslinking, introduces HDDA as the third phase into the lignin-based water phase and PCM oil phase, regulates the interfacial tension relationship between the three phases, forms a double emulsion with lignin as the shell and PCM as the core, and uses this as a template to crosslink the emulsion of the core-shell structure through ultraviolet curing to form a phase change microcapsule with a dense polymer film on the outside, and at the same time utilizes the self-assembly performance of lignin under acidic conditions to achieve the encapsulation of phase change materials, and prepares lignin-based phase change microcapsules with high encapsulation rate and excellent phase change performance. Secondly, a phase change energy storage waterborne polyurethane nanofiber membrane is prepared by an electrospinning process, the surface tension of the waterborne polyurethane emulsion is reduced by a surfactant, and the conductivity of the spinning solution is improved by an electrolyte, thereby improving the spinnability of the waterborne polyurethane. Finally, the plasma technology is used to hydrophobically modify one side of the fiber membrane, giving the fiber membrane asymmetric wettability, improving the water resistance of the fiber membrane, and realizing the unidirectional moisture conduction function. The above preparation process is environmentally friendly and easy to operate, and the prepared phase change energy storage nanofiber membrane can be applied to personal wearable textiles.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The shell monomers formed by the double emulsion template are cross-linked by ultraviolet light-induced free radical polymerization to form a polymer film to encapsulate the phase change material, and lignin self-assembly is used to form lignin-based phase change microcapsules. The use of lignin self-assembly and ultraviolet light cross-linking technology to encapsulate phase change materials to prepare lignin-based phase change microcapsules has high encapsulation efficiency and is not easy to leak, and also realizes the resource utilization and high value of lignin.

[0021] (2) Using silicone water-based polyurethane as raw material and lignin-based phase change microcapsules as phase change materials, aqueous thickeners, surfactants and electrolytes are used to improve the spinnability of the aqueous spinning solution. Nanofiber membranes are prepared through an electrospinning process, which solves the solvent pollution problem caused by traditional electrospinning.

[0022] (3) The membrane is hydrophobically modified by plasma technology, giving the nanofiber membrane asymmetric wettability and unidirectional moisture conduction function. The use of plasma modification technology instead of fluorine-containing emulsion hydrophobic modification avoids the problem of fluoride pollution and reduces the pollution and harm to the environment and human body during the preparation process. The prepared nanofibers are fine and uniform, with good heat storage and heat release properties, strong thermal stability and good air permeability, and have great application potential in the field of PTM intelligent temperature regulating textiles. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The scanning electron microscope (SEM) image and heat flow-temperature change curve (DSC) image of the lignin-based phase change microcapsules prepared in Example 1.

[0024] Figure 2 Scanning electron microscope images (SEM) of the phase change energy storage nanofiber membranes prepared in Example 1 (b) and Comparative Example 1 (a).

[0025] Figure 3 Tensile stress-tensile strain curves of the phase change energy storage nanofiber membranes prepared in Example 1 and Comparative Example 1 (without adding thickener, electrolyte, and surfactant).

[0026] Figure 4 The heat flow-temperature change curves (DSC) of the heat absorption section and the heat release section of the phase change energy storage nanofiber membrane prepared in Example 1 and Comparative Example 2 (without adding phase change microcapsules) are shown.

[0027] Figure 5 This is a comparison diagram of the water drop contact angle (WCA) of the phase change energy storage nanofiber membranes prepared in Example 1, Example 2 and Comparative Example 3 (unmodified).

[0028] Figure 6 The X-ray photoelectron spectroscopy (XPS) of the phase change energy storage nanofiber membranes prepared in Example 1, Example 2 and Comparative Example 3 (unmodified) is shown. DETAILED DESCRIPTION

[0029] The raw materials used in the following examples of the present invention are described as follows: Alkali lignin was purchased from Merck Group, Germany (CAS No.: 8068-05-1), and silicone-modified waterborne polyurethane emulsion was purchased from Guangzhou Dolphin New Materials Co., Ltd.

[0030] The encapsulation efficiency (E) of the phase-change microcapsules involved in the following embodiments of the present invention is p ) is calculated by the following formula: Among them, E c is the PCMs content of phase change microcapsules, ΔH m0 and ΔH c0 are the melting enthalpy and crystallization enthalpy of pure PCMs, ΔH m0 and ΔH c0 are the melting enthalpy and crystallization enthalpy of phase change microcapsules respectively, and φPCMs is the theoretical mass fraction of PCMs in phase change microcapsules.

[0031] After 100 cycles of hot and cold (0℃-50℃-0℃) the retention rate (E r ) is calculated by the following formula: Among them, ΔH0 and ΔH tThey are the phase change enthalpy of the phase change microcapsules before and after 100 hot and cold cycles.

[0032] Example 1 (1) Preparation of lignin-based phase change microcapsules: 1 g of alkali lignin was added to 50 g of NaOH, and 3.5 g of dodecanol (DD) was added at 60 °C. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min to obtain an emulsion. 1 g of 1,6-hexanediol diacrylate (HDDA), 1 g of Span80, and 1 g of 2-hydroxy-2-methylpropiophenone (HMPP) were mixed and added to the emulsion. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min. The pH was adjusted to 2-3 using 0.1 mol / L hydrochloric acid solution. The mixture was then transferred to a magnetic stirrer and stirred at 400 rpm / min while being illuminated with an ultraviolet lamp (wavelength 365 nm, intensity 2000 mW / cm 2 , the distance between the light source and the emulsion was 10 cm) for 15 min to cross-link the HDDA, and finally the phase change microcapsule powder was obtained by spray drying at 150 °C.

[0033] (2) Preparation of spinning solution: Add 3g of polyvinyl alcohol powder (PVA, Mn=100000) to 17g of deionized water, stir evenly at 80℃ for 2h to obtain a 15% PVA solution, and let it stand at room temperature for use. Weigh 12.5g of vinyl triethoxysilane-modified waterborne polyurethane emulsion (WPU, solid content of 50%) and mix it with 12.5g of PVA solution (WPU / PVA=1:1, wt%), and stir evenly at room temperature for 12h to obtain 25g of WPU / PVA solution. Weigh 10g of deionized water, add 0.025g of sodium dodecylbenzene sulfonate (SDBS), 0.025g of sodium chloride (NaCl) and 5.0g of phase change microcapsule powder, ultrasonically disperse for 30min, then stir at 80℃ at 1000rpm / min for 40min, then add 25g of WPU / PVA solution while hot, and continue stirring for 1h to obtain a spinning emulsion.

[0034] (3) Preparation of phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was prepared by emulsion electrospinning technology. The spinning emulsion was transferred to a 10mL syringe and spun for 8 hours using a 17G needle. The specific spinning parameters are as follows: positive high voltage: 17kV, negative high voltage: -1.5kV, spinning distance: 20cm, liquid feed speed: 0.5mm / h, receiving drum speed: 80r / min, the receiver is silicone oil paper; spinning environment temperature: 25℃, humidity: 45%. After spinning, the fiber membrane was transferred to a 35℃ vacuum drying oven and dried for 24 hours to obtain the desired phase change fiber membrane.

[0035] (4) Hydrophobically modified phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was placed in a low-temperature plasma device, placed on a glass plate, and evacuated to a vacuum degree of 1×10 -6 Pa, and when the instrument is stable, C2F4 gas is introduced to perform hydrophobic modification on the surface of the nanofiber membrane. The parameters of the plasma equipment are set as follows: modification power is 75 W, and time is 10 min.

[0036] The phase change enthalpy of the phase change microcapsules prepared according to the above steps is 176.5 J / g, and the encapsulation efficiency is 99.0%. After 100 hot and cold cycles, the phase change enthalpy of the phase change microcapsules is 174.7 J / g, and the retention rate is 99.0%. The contact angle of the phase change energy storage waterborne polyurethane nanofiber membrane is 160°, the crystallization enthalpy is 38.3 J / g, the crystallization temperature is 13.5°C, the melting enthalpy is 43.3 J / g, the melting temperature is 27.5°C, the water pressure resistance is: 14.5 kPa, and the moisture permeability is 2500 g / m 2 ·d, elongation at break is 310%, and tensile strength is 10.5MPa.

[0037] Example 2 (1) Preparation of lignin-based phase change microcapsules: 1 g of alkali lignin was added to 50 g of NaOH, and 3.5 g of dodecanol (DD) was added at 60 °C. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min to obtain an emulsion. 1 g of 1,6-hexanediol diacrylate (HDDA), 1 g of Span80, and 1 g of 2-hydroxy-2-methylpropiophenone (HMPP) were mixed and added to the emulsion. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min. The pH was adjusted to 2-3 using 0.1 mol / L hydrochloric acid solution. The mixture was then transferred to a magnetic stirrer and stirred at 400 rpm / min while being illuminated with an ultraviolet lamp (wavelength 365 nm, intensity 2000 mW / cm 2 , the distance between the light source and the emulsion was 10 cm) for 15 min to cross-link the HDDA, and finally the phase change microcapsule powder was obtained by spray drying at 150 °C.

[0038] (2) Preparation of spinning solution: Add 3g of polyvinyl alcohol powder (PVA, Mn=100000) to 17g of deionized water, stir evenly at 80°C for 2h to obtain a 15% PVA solution, and let it stand at room temperature for use. Weigh 12.5g of vinyl triethoxysilane-modified waterborne polyurethane emulsion (WPU, solid content 50%) and mix it with 12.5g of PVA solution (WPU / PVA=1:1, wt%), and stir evenly at room temperature for 12h to obtain 25g of WPU / PVA solution. Weigh 10g of deionized water, add 0.025g of sodium dodecylbenzene sulfonate (SDBS), 0.025g of sodium chloride (NaCl) and 5.0g of phase change microcapsule powder, ultrasonically disperse for 30min, then stir at 80°C at 1000rpm / min for 40min, then add 25g of WPU / PVA solution while hot, and continue stirring for 1h to obtain a spinning emulsion.

[0039] (3) Preparation of phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was prepared by emulsion electrospinning technology. The spinning emulsion was transferred to a 10mL syringe and spun for 8 hours using a 17G needle. The specific spinning parameters are as follows: positive high voltage: 17kV, negative high voltage: -1.5kV, spinning distance: 20cm, liquid feed speed: 0.5mm / h, receiving drum speed: 80r / min, the receiver is silicone oil paper; spinning environment temperature: 25℃, humidity: 45%. After spinning, the fiber membrane was transferred to a 35℃ vacuum drying oven and dried for 24 hours to obtain the desired phase change fiber membrane.

[0040] (4) Hydrophobically modified phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was placed in a low-temperature plasma device, placed on a glass plate, and evacuated to a vacuum degree of 1×10 -6 Pa, and when the instrument is stable, CF4 gas is introduced to perform hydrophobic modification on the surface of the nanofiber membrane. The parameters of the plasma equipment are set as follows: modification power is 50 W, and time is 10 min.

[0041] The phase change enthalpy of the phase change microcapsules prepared according to the above steps is 176.2 J / g, and the encapsulation efficiency is 99.0%. After 100 cold and hot cycles, the phase change enthalpy of the phase change microcapsules is 174.9 J / g, and the retention rate is 99.0%. The contact angle of the phase change energy storage waterborne polyurethane nanofiber membrane is 153°, the crystallization enthalpy is 38.2 J / g, the crystallization temperature is 13.4°C, the melting enthalpy is 43.5 J / g, the melting temperature is 27.4°C, the water pressure resistance is: 11.5 kPa, and the moisture permeability is 2300 g / m 2 ·d, elongation at break is 300%, and tensile strength is 10.1MPa.

[0042] Example 3 (1) Preparation of lignin-based phase change microcapsules: 1 g of alkali lignin was added to 60 g of NaOH, and 3 g of polyethylene glycol (PEG, Mn = 5000) was added at 60 °C. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min to obtain an emulsion. 3 g of 1,6-hexanediol diacrylate (HDDA), 1 g of Span80, and 1 g of acrylamide diester (AA) were mixed and added to the emulsion. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min. The pH was adjusted to 2-3 using 0.1 mol / L hydrochloric acid solution. The mixture was then transferred to a magnetic stirrer and stirred at 400 rpm / min while being illuminated with an ultraviolet lamp (wavelength 365 nm, intensity 2000 mW / cm 2 , the distance between the light source and the emulsion was 10 cm) for 15 min to cross-link the HDDA, and finally the phase change microcapsule powder was obtained by spray drying at 150 °C.

[0043] (2) Preparation of spinning solution: Add 4g of polyvinyl pyrrolidone powder (PVP, Mn=125000) to 16g of deionized water, stir evenly at 80℃ for 2h to obtain a 20% PVP solution, and let it stand at room temperature for use. Weigh 12.5g of vinyl trimethoxysilane silicone-modified WPU emulsion (solid content of 30%) and mix it with 12.5g of PVP solution (WPU / PVP=1:1, wt%), and stir evenly at room temperature for 12h to obtain 25g of WPU / PVP solution. Weigh 10g of deionized water, add 0.025g of polysorbate (PS), 0.0125g of sodium bisulfite (NAHSO3) and 3.75g of phase change microcapsule powder, ultrasonically disperse for 30min, then stir at 80℃ for 40min at 1000rpm / min, then add 25g of WPU / PVA solution while hot, and continue stirring for 1h to obtain a spinning emulsion.

[0044] (3) Preparation of phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was prepared by emulsion electrospinning technology. The spinning emulsion was transferred to a 10mL syringe and spun for 8 hours using a 17G needle. The specific spinning parameters are as follows: positive high voltage: 16kV, negative high voltage: -1.5kV, spinning distance: 15cm, liquid feed speed: 0.5mm / h, receiving drum speed: 90r / min, the receiver is silicone oil paper; spinning environment temperature: 30℃, humidity: 40%. After spinning, the fiber membrane was transferred to a 35℃ vacuum drying oven and dried for 24 hours to obtain the desired phase change fiber membrane.

[0045] (4) Hydrophobically modified phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was placed in a low-temperature plasma device, placed on a glass plate, and evacuated to a vacuum degree of 1×10 -6Pa, and when the instrument is stable, CF4 gas is introduced to perform hydrophobic modification on the surface of the nanofiber membrane. The parameters of the plasma equipment are set as follows: modification power is 50 W, and time is 5 min.

[0046] The phase change enthalpy of the phase change microcapsules prepared according to the above steps is 202.3 J / g, and the encapsulation efficiency is 98.0%. After 100 hot and cold cycles, the phase change enthalpy of the phase change microcapsules is 200.3 J / g, and the retention rate is 99.0%. The contact angle of the phase change energy storage waterborne polyurethane nanofiber membrane is 142°, the crystallization enthalpy is 25.5 J / g, the crystallization temperature is 24.0°C, the melting enthalpy is 34.0 J / g, the melting temperature is 37.2°C, the water pressure resistance is: 10.5 kPa, and the moisture permeability is 1300 g / m 2 ·d, elongation at break is 305%, and tensile strength is 8.2MPa.

[0047] Example 4 (1) Preparation of lignin-based phase change microcapsules: 1 g of alkali lignin was added to 70 g of NaOH, and 4 g of paraffin wax (PW) was added at 60 °C and homogenized in a homogenizer at 10,000 rpm / min for 3 min to obtain an emulsion. 2 g of 1,6-hexanediol diacrylate (HDDA), 1 g of Span80, and 1 g of trimethylbenzoyl-diphenylphosphine oxide (TPO) were mixed and added to the emulsion, and the mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min. The pH was adjusted to 2-3 using 0.1 mol / L hydrochloric acid solution, and then the mixture was transferred to a magnetic stirrer and stirred at 400 rpm / min while being illuminated with an ultraviolet lamp (wavelength 365 nm, intensity 2000 mW / cm 2 , the distance between the light source and the emulsion was 10 cm) for 15 min to cross-link the HDDA, and finally the phase change microcapsule powder was obtained by spray drying at 150 °C.

[0048] (2) Preparation of spinning solution: Add 2g sodium alginate (SA, Mn=85000) powder to 18g deionized water, stir evenly at 80℃ for 2h to obtain 10% SA solution, and let stand at room temperature for use. Weigh 12.5g γ-glycidyloxypropyltrimethoxysilane silicone-modified WPU emulsion (solid content 35%) and mix with 12.5g SA solution (WPU / SA=1:1, wt%), stir evenly at room temperature for 12h to obtain 25g WPU / SA solution. Weigh 10g deionized water, add 0.0125g fatty acid glyceride (TG), 0.025g hydrogen chloride (HCl) and 5.0g phase change microcapsule powder, ultrasonically disperse for 30min, then stir at 80℃ at 1000rpm / min for 40min, then add 25g WPU / PVA solution while hot, and continue stirring for 1h to obtain spinning emulsion.

[0049] (3) Preparation of phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was prepared by emulsion electrospinning technology. The spinning emulsion was transferred to a 10 mL syringe and spun for 8 hours using a 17G needle. The specific spinning parameters are as follows: positive high voltage: 15 kV, negative high voltage: -1.5 kV, spinning distance: 15 cm, liquid feed speed: 0.5 mm / h, receiving drum speed 70 r / min, receiver is silicone oil paper; spinning environment temperature: 25 ° C, humidity: 45%. After spinning, the fiber membrane was transferred to a 35 ° C vacuum drying oven and dried for 24 hours to obtain the desired phase change fiber membrane.

[0050] (4) Hydrophobically modified phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was placed in a low-temperature plasma device, placed on a glass plate, and evacuated to a vacuum degree of 1×10 -6 Pa, and when the instrument is stable, SF6 gas is introduced to perform hydrophobic modification on the surface of the nanofiber membrane. The parameters of the plasma equipment are set as follows: modification power is 75 W, and time is 10 min.

[0051] The phase change enthalpy of the phase change microcapsules prepared according to the above steps is 163.2 J / g, and the encapsulation efficiency is 99.0%. After 100 cold and hot cycles, the phase change enthalpy of the phase change microcapsules is 160.0 J / g, and the retention rate is 98.0%. The contact angle of the phase change energy storage waterborne polyurethane nanofiber membrane is 150°, the crystallization enthalpy is 40.2 J / g, the crystallization temperature is 24.5°C, the melting enthalpy is 49.5 J / g, the melting temperature is 42.0°C, the water pressure resistance is: 12.2 kPa, and the moisture permeability is 1650 g / m 2 ·d, elongation at break is 280%, and tensile strength is 7.5MPa.

[0052] Example 5 (1) Preparation of lignin-based phase change microcapsules: 1 g of alkali lignin was added to 100 g of NaOH, and 5 g of octadecane (ODE) was added at 60 °C. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min to obtain an emulsion. 3 g of 1,6-hexanediol diacrylate (HDDA), 1 g of Span80, and 1 g of 2,4-diethylthioxanthone (DETX) were mixed and added to the emulsion. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min. The pH was adjusted to 2-3 using 0.1 mol / L hydrochloric acid solution. The mixture was then transferred to a magnetic stirrer and stirred at 400 rpm / min while being illuminated with an ultraviolet lamp (wavelength 365 nm, intensity 2000 mW / cm 2, the distance between the light source and the emulsion was 10 cm) for 15 min to cross-link the HDDA, and finally the phase change microcapsule powder was obtained by spray drying at 150 °C.

[0053] (2) Preparation of spinning solution: Add 3g sodium carboxymethyl cellulose (CMC-Na, Mn=100000) powder to 17g deionized water, stir evenly at 80°C for 2h to obtain a 15% CMC-Na solution, and let stand at room temperature for use. Weigh 12.5g of γ-aminopropylmethyldiethoxysilane silicone-modified WPU emulsion (solid content 45%) and mix with 12.5g CMC-Na solution (WPU / PVA=1:1, wt%), and stir evenly at room temperature for 12h to obtain 25g WPU / CMC-Na solution. Weigh 10g of deionized water, add 0.0125g of polyethylene glycol sulfate (PEGS, Mn=1500), 0.0125g of acetic acid (CH3COOH) and 6.25g of phase change microcapsule powder, ultrasonically disperse for 30min, then stir at 80℃ and 1000rpm / min for 40min, then add 25g of WPU / PVA solution while hot, and continue stirring for 1h to obtain the spinning emulsion.

[0054] (3) Preparation of phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was prepared by emulsion electrospinning technology. The spinning emulsion was transferred to a 10 mL syringe and spun for 8 hours using a 17G needle. The specific spinning parameters are as follows: positive high voltage: 17 kV, negative high voltage: -1.5 kV, spinning distance: 20 cm, liquid feed speed: 0.5 mm / h, receiving drum speed 100 r / min, the receiver is silicone oil paper; spinning environment temperature: 30 ° C, humidity: 40%. After spinning, the fiber membrane was transferred to a 35 ° C vacuum drying oven and dried for 24 hours to obtain the desired phase change fiber membrane.

[0055] (4) Hydrophobically modified phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was placed in a low-temperature plasma device, placed on a glass plate, and evacuated to a vacuum degree of 1×10 -6 Pa, and when the instrument is stable, (CH3)3SIF gas is introduced to perform hydrophobic modification on the surface layer of the nanofiber membrane. The parameters of the plasma equipment are set as follows: modification power is 75 W, and time is 5 min.

[0056] The phase change enthalpy of the phase change microcapsules prepared according to the above steps is 242.6 J / g, and the encapsulation efficiency is 99%. After 100 cold and hot cycles, the phase change enthalpy of the phase change microcapsules is 240.2 J / g, and the retention rate is 99%. The contact angle of the phase change energy storage waterborne polyurethane nanofiber membrane is 140°, the crystallization enthalpy is 52.5 J / g, the crystallization temperature is 15.0°C, the melting enthalpy is 65.5 J / g, the melting temperature is 28.5°C, the water pressure resistance is: 11.5 kPa, and the moisture permeability is 1400 g / m2 ·d, elongation at break is 255%, and tensile strength is 6.8MPa.

[0057] Comparative Example 1 (1) Preparation of lignin-based phase change microcapsules: 1 g of alkali lignin was added to 50 g of NaOH, and 3.5 g of dodecanol (DD) was added at 60 °C. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min to obtain an emulsion. 1 g of 1,6-hexanediol diacrylate (HDDA), 1 g of Span80 and 1 g of 2-hydroxy-2-methylpropiophenone (HMPP) were mixed and added to the emulsion. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min. The pH was adjusted to 2-3 using 0.1 mol / L hydrochloric acid solution. The mixture was then transferred to a magnetic stirrer and stirred at 400 rpm / min while being illuminated with an ultraviolet lamp (wavelength 365 nm, intensity 2000 mW / cm 2 , the distance between the light source and the emulsion was 10 cm) for 15 min to cross-link the HDDA, and finally the phase change microcapsule powder was obtained by spray drying at 150 °C.

[0058] (2) Preparation of spinning solution: Weigh 25 g of vinyl trimethoxysilane silicone-modified WPU emulsion, stir evenly at room temperature for 12 h, weigh 10 g of deionized water, add 5.0 g of phase change microcapsule powder, ultrasonically disperse for 30 min, then stir at 80 °C and 1000 rpm / min for 40 min, then add 25 g of WPU / PVA solution while hot, and continue stirring for 1 h to obtain the spinning emulsion.

[0059] (3) Preparation of phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was prepared by emulsion electrospinning technology. The spinning emulsion was transferred to a 10 mL syringe and spun for 8 hours using a 17G needle. The specific spinning parameters are as follows: positive high voltage: 17 kV, negative high voltage: -1.5 kV, spinning distance: 20 cm, liquid feed speed: 0.5 mm / h, receiving drum speed 80 r / min, and the receiver is silicone oil paper; spinning environment temperature: 25 °C, humidity 45%. After spinning, the fiber membrane was transferred to a 35 °C vacuum drying oven and dried for 24 hours to obtain the desired phase change fiber membrane.

[0060] (4) Hydrophobically modified phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was placed in a low-temperature plasma device, placed on a glass plate, and evacuated to a vacuum degree of 1×10 -6 Pa, and when the instrument is stable, C2F4 gas is introduced to perform hydrophobic modification on the surface layer of the nanofiber membrane. The parameters of the plasma equipment are set as follows: modification power is 75 W, and time is 10 min.

[0061] The phase change enthalpy of the phase change microcapsules prepared according to the above steps is 177.2 J / g, and the encapsulation efficiency is 99.4%. After 100 cold and hot cycles, the phase change enthalpy of the phase change microcapsules is 176.8 J / g, and the retention rate is 99.8%. The contact angle of the phase change energy storage waterborne polyurethane nanofiber membrane is 158°, the crystallization enthalpy is 38.5 J / g, the crystallization temperature is 13.6°C, the melting enthalpy is 43.7 J / g, the melting temperature is 27.1°C, the water pressure resistance is: 14.5 kPa, and the moisture permeability is 2450 / m 2 ·d, elongation at break is 190%, and tensile strength is 1.5MPa.

[0062] Comparative Example 2 (1) Preparation of spinning solution: Add 3g of polyvinyl alcohol powder (PVA, Mn=100000) to 17g of deionized water, stir evenly at 80℃ for 2h to obtain a 15% PVA solution, and let it stand at room temperature for use. Weigh 12.5g of vinyl triethoxysilane-modified waterborne polyurethane emulsion (WPU, solid content 50%) and mix it with 12.5g of PVA solution (WPU / PVA=1:1, wt%), and stir evenly at room temperature for 12h to obtain 25g of WPU / PVA solution. Weigh 10g of deionized water, add 0.025g of sodium dodecylbenzene sulfonate (SDBS), 0.025g of sodium chloride (NaCl) and 5.0g of phase change microcapsule powder, ultrasonically disperse for 30min, then stir at 80℃ at 1000rpm / min for 40min, then add 25g of WPU / PVA solution while hot, and continue stirring for 1h to obtain a spinning emulsion.

[0063] (2) Preparation of phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was prepared by emulsion electrospinning technology. The spinning emulsion was transferred to a 10mL syringe and spun for 8 hours using a 17G needle. The specific spinning parameters are as follows: positive high voltage: 17kV, negative high voltage: -1.5kV, spinning distance: 20cm, liquid feed speed: 0.5mm / h, receiving drum speed 80r / min, and the receiver is silicone oil paper; spinning environment temperature: 25℃, humidity 40%. After spinning, the fiber membrane was transferred to a 35℃ vacuum drying oven and dried for 24 hours to obtain the desired phase change fiber membrane.

[0064] (3) Hydrophobic modified phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was placed in a low-temperature plasma device, placed on a glass plate, and evacuated to a vacuum degree of 1×10 -6 Pa, and when the instrument is stable, CF4 gas is introduced to perform hydrophobic modification on the surface layer of the nanofiber membrane. The parameters of the plasma equipment are set as follows: modification power is 75 W, and time is 10 min.

[0065] The phase-change energy storage waterborne polyurethane nanofiber membrane prepared according to the above steps has a contact angle of 155°, a water pressure resistance of 13.5 kPa, and a moisture permeability of 2300 g / m 2 ·d, elongation at break is 330%, and tensile strength is 10.5MPa.

[0066] Comparative Example 3 (1) Preparation of lignin-based phase change microcapsules: 1 g of alkali lignin was added to 50 g of NaOH, and 3.5 g of dodecanol (DD) was added at 60 °C. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min to obtain an emulsion. 1 g of 1,6-hexanediol diacrylate (HDDA), 1 g of Span80, and 1 g of 2-hydroxy-2-methylpropiophenone (HMPP) were mixed and added to the emulsion. The mixture was homogenized in a homogenizer at 10,000 rpm / min for 3 min. The pH was adjusted to 2-3 using 0.1 mol / L hydrochloric acid solution. The mixture was then transferred to a magnetic stirrer and stirred at 400 rpm / min while being illuminated with an ultraviolet lamp (wavelength 365 nm, intensity 2000 mW / cm 2 , the distance between the light source and the emulsion was 10 cm) for 15 min to cross-link the HDDA, and finally the phase change microcapsule powder was obtained by spray drying at 150 °C.

[0067] (2) Preparation of spinning solution: Add 3g of polyvinyl alcohol powder (PVA, Mn=100000) to 17g of deionized water, stir evenly at 80℃ for 2h to obtain a 15% PVA solution, and let it stand at room temperature for use. Weigh 12.5g of vinyl triethoxysilane-modified waterborne polyurethane emulsion (WPU, solid content 50%) and mix it with 12.5g of PVA solution (WPU / PVA=1:1, wt%), and stir evenly at room temperature for 12h to obtain 25g of WPU / PVA solution. Weigh 10g of deionized water, add 0.025g of sodium dodecylbenzene sulfonate (SDBS), 0.025g of sodium chloride (NaCl) and 5.0g of phase change microcapsule powder, ultrasonically disperse for 30min, then stir at 80℃ at 1000rpm / min for 40min, then add 25g of WPU / PVA solution while hot, and continue stirring for 1h to obtain a spinning emulsion.

[0068] (3) Preparation of phase change fiber membrane: The phase change energy storage waterborne polyurethane nanofiber membrane was prepared by emulsion electrospinning technology. The spinning emulsion was transferred to a 10mL syringe and spun for 8 hours using a 17G needle. The specific spinning parameters are as follows: positive high voltage: 17kV, negative high voltage: -1.5kV, spinning distance: 20cm, liquid feed speed: 0.5mm / h, receiving drum speed: 80r / min, the receiver is silicone oil paper; spinning environment temperature: 25℃, humidity: 45%. After spinning, the fiber membrane was transferred to a 35℃ vacuum drying oven and dried for 24 hours to obtain the desired phase change fiber membrane.

[0069] The phase change enthalpy of the phase change microcapsules prepared according to the above steps is 175.4 J / g, and the encapsulation efficiency is 99%. After 100 hot and cold cycles, the phase change enthalpy of the phase change microcapsules is 175.2 J / g, and the retention rate is 99.9%. The contact angle of the phase change energy storage waterborne polyurethane nanofiber membrane is 122°, the crystallization enthalpy is 38.0 J / g, the crystallization temperature is 13.5°C, the melting enthalpy is 43.8 J / g, the melting temperature is 26.0°C, the water pressure resistance is: 14.5 kPa, and the moisture permeability is 500 g / m 2 ·d, elongation at break is 310%, and tensile strength is 12.3MPa.

[0070] Figure 1 The scanning electron microscope (SEM) and heat flow-temperature change curve (DSC) images of the lignin-based phase change microcapsules prepared in Example 1 show that the particle size of the phase change microcapsules is about 200 nm, and the alkali lignin effectively encapsulates the phase change material. The phase change enthalpy of the prepared phase change microcapsules can reach 171.86 J / g, showing good thermal stability and durability, and the encapsulation rate at different phase change temperatures exceeds 99%.

[0071] Figure 2 The scanning electron microscope images (SEM) of the phase change energy storage water-based polyurethane nanofiber membranes prepared by electrospinning the spinning emulsions of Example 1 and Comparative Example 1 show that when the spinning emulsion does not contain an aqueous thickener, an electrolyte and a surfactant, due to the poor spinnability of WPU, only fibers with a large number of spindle-shaped structures can be obtained after electrospinning, and the fiber morphology is poor. The phase change fibers prepared by electrospinning the emulsion to which an aqueous thickener, an electrolyte and a surfactant are added have a smooth surface and excellent fiber morphology. This indicates that the addition of an aqueous thickener, an electrolyte and a surfactant can effectively improve the spinnability of the WPU emulsion and achieve effective wrapping of the phase change material by WPU.

[0072] Figure 3The stress-strain curves (Tensile stress-Tensile strain) of the phase change energy storage water-based polyurethane nanofiber membranes prepared by electrospinning the spinning emulsions in Example 1 and Comparative Example 1, it can be seen that the mechanical properties of the nanofiber membranes with the addition of aqueous thickeners, electrolytes and surfactants are significantly improved compared with those without the addition of aqueous thickeners, electrolytes and surfactants.

[0073] Figure 4 The heat flow-temperature change curves (DSC) of the heat absorption and heat release sections of the phase change energy storage water-based polyurethane nanofiber membranes prepared in Example 1 and Comparative Example 2 show that the fiber membrane without adding phase change material has no peak on the DSC graph, while the nanofiber membrane with 20% phase change microcapsules added shows good heat storage and heat dissipation effects at around 25°C, and has a relatively high latent heat, demonstrating its application potential in smart wearable textiles for the human body.

[0074] Figure 5 The water droplet contact angle diagram (WCA) of the phase change energy storage water-based polyurethane nanofiber membranes modified with different gas plasmas and without plasma modification in Example 1, Example 2 and Comparative Example 3 shows that since WPU and PVA contain a large number of hydrophilic groups, the water-based polyurethane phase change fiber membrane with WPU / PVA as the fiber matrix has poor water resistance, while the side after plasma modification shows excellent water resistance, and its contact angle is greatly improved, up to 160°, and there is no obvious decrease in the contact angle with time. The different hydrophilicity on both sides of the fiber membrane gives the fiber membrane asymmetric wettability, which can play a role in directional transport of water.

[0075] Figure 6 The X-ray photoelectron spectra (XPS) of the phase change energy storage water-based polyurethane nanofiber membranes after modification with different gas plasmas and without plasma modification in Example 1, Example 2 and Comparative Example 3 show that a new F element appears in the elemental composition after plasma modification, and the proportion of fluorine element changes accordingly with the changes in the modifying gas and the modifying power, which indicates that plasma modification is successfully carried out on the surface of the nanofiber membrane.

[0076] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a phase-change energy storage waterborne polyurethane nanofiber membrane, characterized in that: The following steps are involved: (1) Preparation of lignin-based phase change microcapsules: by weight, add 1 part of alkali lignin to 50-100 parts of sodium hydroxide, then add 2-5 parts of phase change material, and emulsify for 3-10 minutes to obtain an emulsion; mix 1-3 parts of 1,6-hexanediol diacrylate, 1 part of Span80 and 1 part of photoinitiator and add them to the emulsion, continue emulsification for 3-10 minutes, adjust the solution pH to 2-3, irradiate with ultraviolet light for 15 minutes, and finally obtain lignin-based phase change microcapsule powder by spray drying; the wavelength of the ultraviolet light is 365 nm and the intensity is 2000 mW / cm 2 ; (2) preparing a spinning solution: mixing a silicone-modified aqueous polyurethane emulsion, an aqueous thickener, a lignin-based phase change microcapsule powder, a surfactant and an electrolyte, and stirring the mixture at room temperature after ultrasonic dispersion to obtain a spinning solution; (3) Preparing a phase change fiber membrane: injecting the spinning solution into an electrospinning syringe, electrospinning to obtain a nanofiber membrane, and drying to obtain a phase change fiber membrane; (4) Hydrophobic modified phase change fiber membrane: Low-temperature plasma technology is used to perform hydrophobic modification on one side of the phase change fiber membrane.

2. The preparation method according to claim 1, characterized in that: The phase change material in step (1) is one or more of polyethylene glycol, paraffin, dodecanol, and octadecane; the amount of phase change microcapsule powder added is 10-25% of the total mass of the silicone-modified water-based polyurethane emulsion and the water-based thickener; the photoinitiator is one or more of 2-hydroxy-2-methylpropiophenone, acryloyl carboxylic acid diester, trimethylbenzoyl-diphenylphosphine oxide, and 2,4-diethylthioxanthone.

3. The preparation method according to claim 1, characterized in that: The waterborne polyurethane emulsion modified with organic silicon in step (2) is one or more of a waterborne polyurethane emulsion modified with vinyl triethoxysilane, a waterborne polyurethane emulsion modified with vinyl trimethoxysilane, a waterborne polyurethane emulsion modified with γ-glycidyloxypropyl trimethoxysilane, and a waterborne polyurethane emulsion modified with γ-aminopropyl methyl diethoxysilane; the solid content of the waterborne polyurethane emulsion modified with organic silicon is 30-50%.

4. The preparation method according to claim 1, characterized in that: The aqueous thickener in step (2) is one or more of polyvinyl alcohol, sodium alginate, sodium carboxymethyl cellulose, sodium polyacrylate, and polyvinyl pyrrolidone, and the mass fraction of the aqueous thickener is 10-20%; the mass ratio of the silicone-modified aqueous polyurethane emulsion to the aqueous thickener is 1:

1.

5. The preparation method according to claim 1, characterized in that: The surfactant in step (2) is one or more of sodium dodecylbenzene sulfonate, polysorbate, fatty acid glyceride, and polyethylene glycol sulfate; the added amount of the surfactant is 0.05-0.1% of the total mass of the silicone-modified aqueous polyurethane emulsion and the aqueous thickener.

6. The preparation method according to claim 1, characterized in that: The electrolyte in step (2) is one or more of sodium chloride, sodium bisulfite, hydrogen chloride, and acetic acid; the amount of electrolyte added is 0.05-0.1% of the total mass of the silicone-modified aqueous polyurethane emulsion and the aqueous thickener.

7. The preparation method according to claim 1, characterized in that: The parameters of electrospinning in step (3) are as follows: positive high voltage 15~17kV, negative high voltage -1.5kV, spinning distance 15~20cm, propulsion speed 0.5mm / h, receiving roller speed 60~100r / min, and the receiver is a roller covered with silicone oil paper; the spinning environment temperature is 25~30℃, and the humidity is 30~50%.

8. The preparation method according to claim 1, characterized in that: In step (4), the gas for low-temperature plasma hydrophobic modification is one of carbon tetrafluoride, tetrafluoroethylene, sulfur hexafluoride, and trimethylfluorosilane; the low-temperature plasma modification power is 50-75 W, and the modification time is 5-10 min.

9. A phase-change energy storage waterborne polyurethane phase-change fiber membrane prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The phase change temperature of the phase change energy storage waterborne polyurethane phase change fiber membrane is 13.5-28.5°C, the phase change enthalpy is 18.0-65.5 J / g, the water drop contact angle on the hydrophobic side of the plasma-modified phase change fiber membrane is 140-160°, and the moisture permeability is 1300-2500 g / m 2 ·d, tensile strength is 6.5~11.5MPa, and elongation at break is 255~330%.

10. Use of the phase-change energy-storage water-based polyurethane phase-change fiber membrane as claimed in claim 9 in functional textiles.

Citation Information

Patent Citations

  • Double-layer phase-change composite fiber membrane as well as preparation method and application thereof

    CN116988225A

  • Method for preparing modified WPU (Waterborne Polyurethane) coating film

    CN106750162A

  • Preparation method of bio-based high-performance waterborne polyurethane resin and product thereof

    CN112430308A

  • Waterborne polyurethane waterproof moisture-permeable film and preparation method thereof

    CN116752284A

  • Ag / TiO2 lignin-based carbon fiber membrane as well as preparation method and application thereof

    CN116764627A

Cited By

  • Preparation method of waterproof moisture-permeable film for outdoor clothes

    CN119980570A

  • Composite nanofiber membrane with bidirectional thermal management and preparation method thereof

    CN121381279A

  • Composite nanofiber membrane with bidirectional thermal management and method of making the same

    CN121381279B

  • Two-component polyurethane adhesive for OSB (oriented strand board) and application of two-component polyurethane adhesive

    CN121537914A